2000
DOI: 10.1007/s004040000080
|View full text |Cite
|
Sign up to set email alerts
|

Mullerian adenosarcoma of the uterus associated with tamoxifen therapy

Abstract: Mullerian adenosarcoma of the uterus is a biphasic tumor exhibiting benign epithelial and malignant stromal component. This tumor may occasionally be associated with tamoxifen therapy which is used as an adjuvant drug for breast carcinoma. Reviewing the literature, we found only 12 adenosarcoma cases associated with tamoxifen therapy Thus, the clinical and pathological findings in a 58 years old postmenopausal woman who developed uterine adenosarcoma, following low dose tamoxifen therapy after 8 years, was dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 0 publications
1
18
0
3
Order By: Relevance
“…[5][6][7] Some studies suggest that the use of tamoxifen may have a role in the pathogenesis of adenosarcoma. [8][9][10][11] The prognosis of adenosarcoma greatly depends on stage and the presence of sarcomatous overgrowth. 12 A small series of cases 13 found that the 2-year progression-free and overall survival rates for tumors with sarcomatous overgrowth were 20% compared with 100% for adenosarcoma lacking sarcomatous overgrowth.…”
mentioning
confidence: 99%
“…[5][6][7] Some studies suggest that the use of tamoxifen may have a role in the pathogenesis of adenosarcoma. [8][9][10][11] The prognosis of adenosarcoma greatly depends on stage and the presence of sarcomatous overgrowth. 12 A small series of cases 13 found that the 2-year progression-free and overall survival rates for tumors with sarcomatous overgrowth were 20% compared with 100% for adenosarcoma lacking sarcomatous overgrowth.…”
mentioning
confidence: 99%
“…By far, the most common uterine malignancy in tamoxifen-treated patients is endometrial adenocarcinoma. 3,4 Additionally, MMMTs, including Mullerian adenosarcomas, have also been reported to be related to tamoxifen therapy. 3 Uterine sarcomas is a heterogeneous rare group of neoplasm with a 3-7% incidence among uterine cancers and a 1-3% incidence among all gynecological cancers.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Additionally, MMMTs, including Mullerian adenosarcomas, have also been reported to be related to tamoxifen therapy. 3 Uterine sarcomas is a heterogeneous rare group of neoplasm with a 3-7% incidence among uterine cancers and a 1-3% incidence among all gynecological cancers. This type of cancer is divided into the following pathologic types: carcinosarcomas (50%), leiomyosarcomas (30%), endometrial stromal sarcomas (10-15%), and adenosarcomas (5-10%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L'importance de la dissémination métastatique ré-sulte de ce qu'elle se fait par voie lymphatique liée au contingent épithélial et par voie sanguine due au contingent sarcomateux. Comme cela est précisé dans cet article, certains adéno-et carcinosarcomes surviennent sous traitement par tamoxifène [3][4][5]. Cet antiestrogène, administré chez les femmes ayant un cancer du sein positif pour les récepteurs aux estrogènes, peut induire une action estrogé-nique paradoxale.…”
unclassified